La neuroética y la naturalización de la filosofía moral - Braun Gutiérrez, Ricardo (2014)
In this article I discuss the possibility of the naturalization of moral philosophy incorporating recent discussions in neuroethics. As a working hypothesis, one could argue that neuroethics may serve as an empirical basis for the moral justification of criteria that any mature moral theory may have. I defend the thesis that any form of naturalization in contemporary science should embrace a form of a broad naturalization in contrast to a strict naturalization which characterizes the classic dichotomy natural/human sciences. Finally, I discuss some characterization of neuroethics, in the sense of neuroscience of ethics—as different to ethics of neuroscience—and its relationship to the possibility of the naturalization of morality, and discuss some reasons to be cautious about the neurological findings and their interpretation particularly with functional neuroimaging techniques.